2014
DOI: 10.1148/radiol.14132187
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Texture Analysis of Persistent Part-Solid Ground-Glass Nodules: Differentiation of Preinvasive Lesions from Invasive Pulmonary Adenocarcinomas

Abstract: In part-solid GGNs, higher kurtosis and smaller mass are significant differentiators of preinvasive lesions from IPAs, and preinvasive lesions can be accurately differentiated from IPAs by using computerized texture analysis. Online supplemental material is available for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
144
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(156 citation statements)
references
References 29 publications
6
144
2
Order By: Relevance
“…Nevertheless, texture analysis on radiological data has nowadays become an integral part of an emerging field call radiomics, a high-throughput process in which large amounts of advanced quantitative imaging features are extracted and integrated for predictive or prognostic purpose (6)(7)(8). Some research groups have developed texture analysis methods to quantify lesion heterogeneity on lung CT (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, texture analysis on radiological data has nowadays become an integral part of an emerging field call radiomics, a high-throughput process in which large amounts of advanced quantitative imaging features are extracted and integrated for predictive or prognostic purpose (6)(7)(8). Some research groups have developed texture analysis methods to quantify lesion heterogeneity on lung CT (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Higher entropy indicates increased lesion heterogeneity (12). Several studies have shown that entropy extracted from medical images may add value in assessment of tissue morphologic changes induced by various diseases, including adnexal neoplasms (13,14), liver cirrhosis (15), and lung diseases (10,16). Grove et al (17) and Gatenby et al (18) first introduced a new heterogeneity metric by using entropy difference of CT attenuation across the tumor core to boundary regions and found it could predict patient survival in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…to compute the size of solid part in a part-solid GGO nodule by EM algorithm if the GGO nodules are part-solid one. (5). to calculate the size of GGO nodules.…”
Section: Algorithm Of the Feature Extractionmentioning
confidence: 99%
“…In lung nodules, there are two types. One is solid nodules, and the other is Ground-Glass Opacity (GGO) nodules [5]. Currently, some approaches [6], [7] have been proposed to detect lung cancer based on some features of solid nodules [8] by image processing methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation